Modeling and Analysis of Inductive Coil ELF Sensor - Rajendra Aparnathi; Vedvyas Dwivedi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Mathematical statistical analysis of inductive loop coil-sensor is carried out for its magnetic field effects operating on extremely low frequency (